2023
DOI: 10.1186/s13048-023-01134-0
|View full text |Cite
|
Sign up to set email alerts
|

AMH producing purely cystic virilizing adult granulosa cell tumor in 17 years old girl: a case report and review of literatures

Abstract: Background Androgen-producing granulosa cell tumor in adolescent girl is rare condition and clinical characteristics are not fully elucidated. Case presentation Seventeen years old girl complained of secondary amenorrhea was referred to our out-patient consultation. Markedly elevated serum testosterone, LH, and AMH levels were noted. Mild hirsutism and clitoromegaly were presented. Transabdominal ultrasonography and MRI revealed cystic mass occupie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Immunohistochemistry has confirmed that the tumor cells are negative for LH. [ 10 , 11 ] Some researchers have hypothesized that tumor cells produce factors that stimulate tumor is high. [ 6 ] In women with markedly elevated levels of T or its precursor androstenedione and normal levels of dehydroepiandrosterone, an androgen-secreting ovarian tumor is likely.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Immunohistochemistry has confirmed that the tumor cells are negative for LH. [ 10 , 11 ] Some researchers have hypothesized that tumor cells produce factors that stimulate tumor is high. [ 6 ] In women with markedly elevated levels of T or its precursor androstenedione and normal levels of dehydroepiandrosterone, an androgen-secreting ovarian tumor is likely.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Immunohistochemistry has confirmed that the tumor cells are negative for LH. [ 10 , 11 ] Some researchers have hypothesized that tumor cells produce factors that stimulate the adenohypophysis to secrete a large amount of LH. [ 11 ] LH secretion is regulated by both the hypothalamus and pituitary gland.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations